Studying the photodegradation of ethylcellulose and methylcellulose in the presence and absence of benzophenone (BPh) (Journal of the College of Basic Education, 2022)
The induced photodegradation of ethylcellulose (EC) andmethylcellulose (MC) films in air was investigated in the presence andabsence of benzophenone (BPh) (photosensitizer) by acceleratedweathering tester. The addition of (0.2wt %) of benzophenone (BPh) tocellulose derivatives films (25µm in thickness) enhanced thephotodegradation of the ethylcellulose (EC) more than methylcellulose(MC) films.The photodegradation rate was followed by increase incarbonyl absorbance of polymers and decomposition rate constant (k d ) ofbenzophenone in polymers using I.R and U.VVis. spectra respectively. According to the kinetic data and spectra results, the inducedphotodegradation mechanisms of cellulose derivatives films weresuggested under the experimental conditions employed usingu.v.radiation at λ = 313 nm , light intensity 3.49*10 5 einsteins.dm 3 .S 1 attemperature 45 o C.